Endovascular treatment of cerebral arteriovenous malformations following radiosurgery. - Marks, M P; Lane, B; Steinberg, G K; Fabrikant, J I; Levy, R P; Frankel, K A; Phillips, M H (American Journal of Neuroradiology, 1993)
PURPOSE Previous reports of embolization of cerebral arteriovenous malformations (AVMs) have evaluated the technique as adjunctive therapy prior to surgery or radiosurgery; our aim is to assess the role of embolization following radiosurgery.PATIENTS Six patients previously treated with radiosurgery and showing no response as judged by cerebral angiography were embolized 24 to 55 months (mean 34.3 months) after initial radiosurgery.RESULTS In five of six, a significant volume reduction was achieved ranging from 60%-100% (mean 74%). One patient was treated with embolization alone and the AVM has remained fully thrombosed 2 years after treatment. Three patients underwent surgical resection for cure after embolization, and two patients had repeat radiosurgery to a significantly smaller AVM volume. One patient had an asymptomatic carotid dissection at embolization; however, no clinically apparent complications occurred in the treatment group.CONCLUSION Embolization can be used after radiosurgery to assist in the management of those AVMs that have not responded to initial treatment.